Comparative characteristics of functional coordination and force readiness boys 8—9 grades - Іващенко, О. В.; Пашкевич, С. А.; Крінін, Ю. В. (Physical Education Theory and Methodology, 2014)
Purpose — to determine the characteristics of functional and motor fitness guys eighth and ninth grades. Material and methods. To achieve the objectives following methods were used: analysis of scientific literature, teacher testing and statistical methods of processing the results of the study. The study involved 17 boys 8th grade, 17 children in grade 9. Conclusions. The guys 8—9 classes standardized canonical discriminant function coefficients enable us to determine the relative contributions of the variables in the function result. Most contribution to the canonical function are changeable 1, 5 and 2: the larger the values of these variables, the greater the value of the function. The above indicates the possibility of evaluating the functional readiness of pupils of 8—9 classes with the help of samples Stange, Genchi and Serkin. The guys 8—9 classes standardized canonical discriminant function coefficients, which allow us to determine the relative contributions of the variables in the function result. Most contribution to the canonical function variables are 8, 7 and 9: the higher the values of these variables, the greater the value of the function. The above indicates the possibility of assessment of motor readiness of pupils of 8—9 classes by means of tests 8, 7 and 9. The boys grades 8—9 structural factors canonical discriminant function show that the most significant feature is associated with 8 and 9 variables: the more attention is paid to the static speed and power, the greater the likelihood improve motor fitness children grades 8—9.